Current Developments in Web Based Learning ICWL 2015 International Workshops, KMEL, IWUM, LA, Guangzhou, China, November 5-8, 2015, Revised Selected Papers - Gong, Zhiguo; Chiu, Dickson K. W.; Zou, Di (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the thoroughly revised selected papers of the workshops of the 14th International Conference of Web Based Learning, ICWL 2015, held in Guangzhou, China, in November 2015. This volume comprises papers of three workshops: 1. The 5th International Symposium on Knowledge Management and E-Learning, KMEL 2015 2. The first International Workshop on User Modeling for Web Based Learning, IWUM 2015 3. The International Workshop on Learning Analytics.